Living‐donor liver transplantation for mild Zellweger spectrum disorder: Up to 17 years follow‐up. (16th February 2018) - Demaret, Tanguy; Varma, Sharat; Stephenne, Xavier; Smets, Françoise; Scheers, Isabelle; Wanders, Ronald; Van Maldergem, Lionel; Reding, Raymond; Sokal, Etienne
Abstract: Mild Zellweger spectrum disorder, also described as Infantile Refsum disease, is attributable to mutations in PEX genes. Its clinical course is characterized by progressive hearing and vision loss, and neurodevelopmental regression. Supportive management is currently considered the standard of care, as no treatment has shown clinical benefits. LT was shown to correct levels of circulating toxic metabolites, partly responsible for chronic neurological impairment. Of three patients having undergone LT for mild ZSD, one died after LT, while the other two displayed significant neurodevelopmental improvement on both the long‐term (17 years post‐LT) and short‐term (9 months post‐LT) follow‐up. We documented a sustained improvement of biochemical functions, with a complete normalization of plasma phytanic, pristanic, and pipecolic acid levels. This was associated with stabilization of hearing and visual functions, and improved neurodevelopmental status, which has enabled the older patient to lead a relatively autonomous lifestyle on the long term. The psychomotor acquisitions have been markedly improved as compared to their affected siblings, who did not undergo LT and exhibited a poor neurological outcome with severe disabilities. We speculate that LT performed before the onset of severe sensorineural defects in mild ZSD enables partial metabolic remission and improved long‐term clinical outcomes.